The role of local political parties as political education in north aceh: a study of aceh party - Rusli Yusuf, M. Akmal, Misri A. Muchsin, T. M. Jamil,; Saputra, Jumadil (Opción, 2019)
This study aims to provide in-depth and comprehensive descriptions regarding the role of local political parties in carrying out political education for the elite, cadres and the community. This research used a qualitative analysis with descriptive analytic methods. The results of this study showed that the Aceh Party had organized political education but had not yet maximized its implementation mechanism. The level of role is at the level of Role-Expectancy. In conclusion, the role of the Aceh Party in the North Aceh region is not yet in a dimension of role-perception.